Research on precision shaping technology of CVT for fairway cBN grinding wheel - Xiangguo QIN; Ziying ZHANG; Dongsheng TANG (Jin'gangshi yu moliao moju gongcheng)
ObjectivesCVT technology has the advantages of a simple and compact structure, low cost, and convenient operation. It is the most ideal automobile transmission. The processing of its core component—the pulley block—is a difficult point in CVT manufacturing, especially the processing of the ball track on the pulley and pulley shaft. Electroplated cBN grinding wheels have the advantages of a high grinding ratio, low grinding force, less heat, environmental friendliness and good consistency in machining accuracy. They are ideal grinding tools for raceway machining. However, due to the high geometric accuracy required for the raceway—especially the allowable tolerance of the contact angle and its narrowness—it brings great difficulties to the precision dressing quality of the grinding wheel. Therefore, the precision forming and truing technology of cBN grinding wheels for CVT pulley raceway forming grinding is one of the key technologies that restrict the progress of CVT gearbox manufacturing technology in China. MethodsBased on the technical problems existing in the current optical guided dressing method in engineering, this paper analyzes the principle of raceway forming grinding and the geometric feature structure of the raceway, and combs through the geometric accuracy control principle of the cBN grinding wheel in raceway grinding. The proportional dressing method is proposed and adopted. The feasibility of the method is verified by a dressing experiment. It is verified that the contact angle error of the raceway grinding wheel can be stably controlled within ± 1°, and the contact angle deviation of the left and right arcs is less than 1°.Results(1) The dresser "cross + ceramic grinding wheel up and down reciprocating" tool grinding wheel dressing method, can ensure that each point on the arc of the ceramic grinding wheel contacts the highest point on the cylindrical surface of the grinding wheel being dressed. This method is beneficial for ensuring the sharp angle dressing accuracy of the ceramic grinding wheel. The R value accuracy of arc dressing of the ceramic grinding wheel can reach 0.9980 and 1.0020 mm, and the arc profile accuracy can reach 0.002 and 0.003 mm. (2) Within the tolerance range, the change of contact angle α with Xi and Rg is approximately linear, and the smaller the tolerance range, the better the straightness. (3) During the dressing process of the electroplated cBN grinding wheel in CVT raceway grinding, as the dressing process continues, the arc loss at the tip of the ceramic grinding wheel increases, and the arc values on both sides of the cBN grinding wheel gradually increase, resulting in a smaller contact angles on both sides. In the actual machining process, the dressing results can be detected in time, and the contact angle dressing accuracy can be controlled by adjusting the compensation value of the controller. The arc wear of the ceramic grinding wheel tip has little effect on the center distance of the double arcs on both sides of the tooth profile of the cBN grinding wheel. (4) When the ceramic diamond grinding wheel is used to dress the cBN grinding wheel, arc wear of at the ceramic grinding wheel tip is inevitable. In fact, a binder with better wear resistance can be selected, or the diameter of the grinding wheel can be increased to reduce the influence of ceramic grinding wheel wear on dressing quality. When adjusting the program, the contact angle is adjusted to a negative difference, and the allowable wear amount of the tool grinding wheel is increased to prolong the service time of the tool grinding wheel. ConclusionsDue to factors such as drawing accuracy, minimum feed, and operation experience, the optical guidance method has problems such as poor trimming accuracy, time-consuming and laborious programming correction. At the same time, this method results in a low degree of smoothness in the grinding wheel contour, and sharp points often appear on the surface.This can easily cause quality problems such as scratches on the pulley ball track or unstable quality when the cBN grinding wheel grinds the ball track. Based on the optical-guided dressing method, this paper proposes a proportional dressing method. The dressing process of the grinding wheel is adjusted by the proportional adjustment principle, which can effectively control the dressing results. The dressing method of the tool grinding wheel using the dresser "cross + ceramic grinding wheel up and down" ensures that all points on the arc of the ceramic grinding wheel are in contact with the highest point on the outer cylindrical surface of the dressing grinding wheel being dressed. This method is conducive to ensuring the sharp angle dressing accuracy of the ceramic grinding wheel.